Nitrogen fertilization on sugar beet transplanted in Peruvian highlands - Paz-Ayala, Pedro (2023)
In Peruvian highlands, in Humid Sub Tropical Montane Forest and in Very Humid Montane Grassland, where 1’000,000 ha could be incorporated to agriculture, transplanted sugar beet (Beta vulgaris L.) was studied. An experiment at 3 242 masl, with one cultivar of sugar beet and with densities of 100 000, 150 000, and 200 000 plants per hectare, and doses of 20, 120, and 220 kg N ha-1 were studied; another one with three cultivars of sugar beet was made at 4043 masl where doses of 0, 100, 200, and 300 kg N ha-1 were studied. With fodder beet it was at 3 121 masl, with one cultivar, and densities of 230 000, and 300 000 plants per hectare and doses of 24, 144, and 264 kg N ha-1. All experiments had blocks complete randomized design with four replications. Sugar and fodder beet in early transplanted plants showed a normal development till three months age and resistance to freezing. Yield of sugar beet was highly with 200 thousand plants per hectare. There were not significantly differences (p > 0.05) in yields with nitrogen doses, nor in sucrose, brix, or purity. Bromatological analysis of leaves and crowns of sugar beet shows that is a good aliment for livestock feed. Late transplanting affected roots development and nitrogen fertilization response. Fodder beet showed differences (p < 0.05) between densities having 300000 plants per hectare more yield.